The Hadith (Beating Children on Account of Leaving Prayer) Between Prove and Non- Prove - Wahab, Bahzad K.; Ibrahim, Sulaiman S.; Abdulghani, Aumed M. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2024)
This research deals with (beating children on account of leaving prayer) from its narration because there are those who deny the proof and authenticity of this Hadith. It is clear if the proof of the evidence has been abolished it’s pretext will also be abolished. To prove the existence of this Hadith we have extracted it from the Suna codification which composed of Alsahah, the precepts, references and dictionaries. We have discussed syllables of Hadith. We have also discussed the ruling of Hadith by reliance on higher grand authors of Hadith from among those who came before, later or contemporary. The measurements of all narrations and Hadith methods which higher grand scholars made it acceptable is considered proven and those which are rejected are dispelled and considered unacceptable on the rule of any matter on which a text has been provided and especially if the matter of the Hadith is concerned Islam as a whole and prayer as one of the most pillars of it. Throughout this we have retorted to those who cast doubt on the authenticity of the Hadith and its proof. We have also identified what is weak and what is proven. The research has been concluded with the most important finding of the study.